menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
5y - 3z + 4y -1z - 3y; y = 3 and z = -2
asked
Dec 25, 2018
221k
views
2
votes
5y - 3z + 4y -1z - 3y; y = 3 and z = -2
Mathematics
high-school
Lal Krishna
asked
by
Lal Krishna
6.9k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
2
votes
5(3)-3(-2)
15-(-6)=
15+6=21
a negative plus a negative is a positive so its 21
4(3)-3(-2)
12-(-6)
12+6=18
21+18=39
Sebastian Z
answered
Dec 29, 2018
by
Sebastian Z
6.1k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
7.2m
questions
9.7m
answers
Other Questions
Write words to match the expression. 24- ( 6+3)
Please solve the following equation. x-6x=56
whats the most accurate estimation of 65+77
Find the additive inverse of 18/23
What is 25% of 500.00
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org